1991
DOI: 10.1128/jb.173.20.6339-6346.1991
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GroEL in nif gene regulation and nitrogenase assembly

Abstract: Several approaches were used to study the role of GroEL, the prototype chaperonin, in the nitrogen fixation (nij) system. An Escherichia coli groEL mutant transformed with the Klebsiella pneumoniae nif gene cluster accumulated very low to nondetectable levels of nitrogenase components compared with the isogenic wild-type strain or the mutant cotransformed with the wild-type groE operon. In K. pneumoniae, overexpression of the E. coli groE operon markedly accelerated the rate of appearance of the MoFe protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…It was, therefore, concluded that the nifS gene product, together with the products of several other nif genes, is required for the activities of all three nitrogenase systems inAzotobacter vinelandii, perhaps by stabilizing the nitrogenases against oxidative inactivation (14). Interestingly, it was reported that when K pneumoniae nif genes were introduced into E. coli, the assembly of the nitrogenases required the E. coligroEL gene product, which is a major molecular chaperone involved in many cellular functions (9). Recently, the nifS gene product from Azotobacter vinelandii has been overproduced and purified (36).…”
Section: Discussionmentioning
confidence: 99%
“…It was, therefore, concluded that the nifS gene product, together with the products of several other nif genes, is required for the activities of all three nitrogenase systems inAzotobacter vinelandii, perhaps by stabilizing the nitrogenases against oxidative inactivation (14). Interestingly, it was reported that when K pneumoniae nif genes were introduced into E. coli, the assembly of the nitrogenases required the E. coligroEL gene product, which is a major molecular chaperone involved in many cellular functions (9). Recently, the nifS gene product from Azotobacter vinelandii has been overproduced and purified (36).…”
Section: Discussionmentioning
confidence: 99%
“…In a portion of the nodules induced by the groEL1 mutant, the endosymbionts differentiated to elongated bacteroids; however, the nodules were not functional and nitrogen fixation activity was not detected. GroEL is required for nitrogenase assembly in other bacteria (22). Thus, likewise, in the absence of GroEL1, subunits of nitrogenase may not form an active enzyme complex.…”
Section: Ncr247-ribosomal Protein Interactions: Modulation Of the Bacmentioning
confidence: 99%
“…Unfortunately, commercially available E. coli GroES antibodies showed extensive nonspecific crossreactivity with these solutions and were therefore not helpful in this regard. Since the early 1990s, when GroEL research was in its infancy, several reports have appeared suggesting that GroEL might have something to do with nitrogenase regulation and assembly (40)(41)(42)(43)(44). For example, 35 S pulse-chase experiments with Klebsiella pneumoniae suggested transient binding of newly synthesized Fe protein and MoFe protein polypeptides to GroEL.…”
Section: Resultsmentioning
confidence: 99%